Helmet use in BIXI cyclists in Toronto, Canada: an observational study. Issue 3 (18th June 2012) - Bonyun, Marissa; Camden, Andi; Macarthur, Colin; Howard, Andrew
Abstract : Objective: To investigate the use of helmets for cyclists choosing to use BIXI bikes in comparison to personal bike riders in the City of Toronto. Design: Cross-sectional study design. Setting: Cyclists were observed in Toronto, Canada. Participants: Of the 6732 sample size, 306 cyclists on BIXI bikes and 6426 personal bike riders were observed. Outcome measure: The outcome of interest was helmet use. Results: Overall, 50.3% of cyclists wore helmets. The proportion of BIXI bike riders using helmets was significantly lower than the proportion of helmet users on personal bikes (20.9% vs 51.7%, respectively, p<0.0001). Conclusions: Although the BIXI bike programme has provided an alternate means for Torontonians to use a bicycle, cyclists using BIXI bikes are much less likely to wear a helmet. Since the prevalence of helmet use in cyclists in general is already low, helmet use should be especially promoted in BIXI bike riders in order to promote a safe and healthy environment for cyclists.